MRNA vaccines against H10N8 and H7N9 influenza viruses of pandemic potential are immunogenic and well tolerated in healthy adults in phase 1 randomized clinical trials. Issue 25 (31st May 2019) - Feldman, Robert A.; Fuhr, Rainard; Smolenov, Igor; (Mick) Ribeiro, Amilcar; Panther, Lori; Watson, Mike; Senn, Joseph J.; Smith, Mike; Almarsson, Ӧrn; Pujar, Hari S.; Laska, Michael E.; Thompson, James; et al.
Highlights: mRNA vaccines may provide timely and effective responses to threats from emerging pathogens. We assessed mRNA vaccines against 2 highly pathogenic avian influenza strains. The first mRNA N10N8 and H7N9 influenza vaccines are safe and immunogenic. Abstract: Background: We evaluated safety and immunogenicity of the first mRNA vaccines against potentially pandemic avian H10N8 and H7N9 influenza viruses. Methods: Two randomized, placebo-controlled, double-blind, phase 1 clinical trials enrolled participants between December 2015 and August 2017 at single centers in Germany (H10N8) and USA (H7N9). Healthy adults (ages 18–64 years for H10N8 study; 18–49 years for H7N9 study) participated. Participants received vaccine or placebo in a 2-dose vaccination series 3 weeks apart. H10N8 intramuscular (IM) dose levels of 25, 50, 75, 100, and 400 µg and intradermal dose levels of 25 and 50 µg were evaluated. H7N9 IM 10-, 25-, and 50-µg dose levels were evaluated; 2-dose series 6 months apart was also evaluated. Primary endpoints were safety (adverse events) and tolerability. Secondary immunogenicity outcomes included humoral (hemagglutination inhibition [HAI], microneutralization [MN] assays) and cell-mediated responses (ELISPOT assay). Results: H10N8 and H7N9 mRNA IM vaccines demonstrated favorable safety and reactogenicity profiles. No vaccine-related serious adverse event was reported. For H10N8 (N = 201), 100-µg IM dose induced HAI titers ≥ 1:40 in 100% and MN titers ≥ 1:20 in 87.0% of participants. The 25-µg intradermal dose induced HAI titers > 1:40 in 64.7% of participants compared to 34.5% of participants receiving the IM dose. For H7N9 (N = 156), IM doses of 10, 25, and 50 µg achieved HAI titers ≥ 1:40 in 36.0%, 96.3%, and 89.7% of participants, respectively. MN titers ≥ 1:20 were achieved by 100% in the 10- and 25-µg groups and 96.6% in the 50-µg group. Seroconversion rates were 78.3% (HAI) and 87.0% (MN) for H10N8 (100 µg IM) and 96.3% (HAI) and 100% (MN) in H7N9 (50 µg). Significant cell-mediated responses were not detected in either study. Conclusions: The first mRNA vaccines against H10N8 and H7N9 influenza viruses were well tolerated and elicited robust humoral immune responses. ClinicalTrials.govNCT03076385 andNCT03345043 .